Molecular characterization of canine parvovirus in Vientiane, Laos - Vannamahaxay, Soulasack; Vongkhamchanh, Souliya; Intanon, Montira; Tangtrongsup, Sahatchai; Tiwananthagorn, Saruda; Pringproa, Kidsadagon; Chuammitri, Phongsakorn (Archives of virology, 2017)
The global emergence of canine parvovirus type 2c (CPV-2c) has been well documented. In the present study, 139 rectal swab samples collected from diarrheic dogs living in Vientiane, Laos, in 2016 were tested for the presence of the canine parvovirus (CPV) VP2 gene by PCR. The results showed that 82.73% (115/139) of dogs were CPV positive by PCR. The partial VP2 gene was sequenced in 94 of the positive samples; 91 samples belonged to CPV-2c (426Glu) subtype, while 3 samples belonged to the CPV-2a (426Asn) subtype. Notably, phylogenetic analysis of amino acid sequences revealed a close relationship between Laotian isolates and novel Chinese CPV-2c isolates. In Laotian CPV isolates, aligned protein sequences indicated a high rate of residue substitutions at positions 305, 324, 345, 370, 375, and 426 in the GH loop. The mutation at residue 370 (Q370R), a single mutation, was characterized as a unique mutant residue specific to the Laotian CPV-2c variant.